Making a PAC: payments for agrobiodiversity conservation services - Drucker, Adam G. (WRENMedia, 2012)
The majority of the planet's food comes from a very small number of crops: only around 30 account for more than 85 per cent of global crop production. Of the about 350,000 plant species known to exist, fewer than 20 per cent are eaten and only some 150 have been domesticated for farming. Furthermore, crops' genetic diversity within species is very narrow and existing agrobiodiversity is being lost at a rapid rate. However, a recent pilot scheme to pay farmers for conserving traditional crop varieties has provided a promising way to stem the loss.